Distribution of a novel 57 kDa intermediate filament (IF) protein in the nervous system - Parysek, LM (J Neurosci, 1988)
A 57 kDa protein, that is not vimentin, is the major component of intermediate filaments (IF) obtained after 2 cycles of in vitro assembly from PC12 cells (Parysek and Goldman, 1987). By use of an antiserum to the 57 kDa protein, a cross-reacting antigen (of identical molecular weight) was detected on immunoblots of IF preparations and by immunofluorescence of various rat tissues. Immunolocalization studies on 3–4 micron frozen sections of tongue, small intestine, and adrenal gland showed bright labeling of nerve bundles and fine-caliber nerve fibers. The chromaffin cells and ganglion cells of the adrenal medulla also were labeled. In the nervous system, intense labeling was seen in small-caliber nerve fibers in sciatic nerve and spinal cord dorsal roots, as well as in the dorsal white columns and dorsal root ganglia. Of the ganglion cells, preferential labeling was seen in small-sized ganglion cells, whereas a monoclonal antibody to the 150 and 200 kDa neurofilament triplet (NFT) components labeled the large-sized ganglion cells. In the areas of the brain thus far examined with 57 kDa antiserum, there was labeling of components of cranial nerves and labeling of thin fibers in several areas, including the granular layer of the cerebellum and the corticospinal tract in the brain stem. For each tissue, adjacent sections treated with vimentin or glial fibrillary acidic protein antibody revealed labeling patterns distinct from that seen with either the 57 kDa or NFT antibodies. These results indicate that the 57 kDa IF protein is a neural IF component. Furthermore, this protein is distributed in only certain neuronal elements; these elements may be unified by an as yet unrecognized pattern of function in the nervous system.